Uji Efek Antidepresan Ekstrak Metanol Jamur Tlethong (Psilocybe cubensis) Pada Tikus Putih Jantan (Rattus norvegicus): ditinjau dari Immobility Time Dengan Metode Forced Swim Test - Kurama, Nofri P.; Bodhi, Widdhi; Wiyono, Weny (UNIVERSITAS SAM RATULANGI, 2013)
ABSTRACTTlethong mushroom (Psilocybe cubensis) contains psilocybin that potential as antidepressant.The aim of this research was to examine the effect of Tlethong extract as antidepressant onwhite male wistar (Rattus norvegicus). Antidepressant test were evaluate on white malewistar which divided into 5 groups. The first group were administered with aquadest asnegative control, Second group were administered with amitriptilin as positive control, thirdgroup were administered with Tlethong extract with dose 500 mg/KgBB, 625 mg/KgBB and750 mg/KgBB then tail suspension test were conducted. Immobility time dengan metodeforced swim test. Obtained data were analyzed by one way ANOVA. The result shows thatTlethong extract possess antidepressant activity evaluated by its immobility time using forcedswim test method.Keywords: Antidepressant, immobility time, forced swim test, tail suspension test, Psilocybecubensis